2018
DOI: 10.1111/hepr.13249
|View full text |Cite
|
Sign up to set email alerts
|

Proton pump inhibitor therapy does not increase serum endotoxin activity in patients with cirrhosis

Abstract: Our results suggest that PPI usage does not have a significant impact on serum levels of gut-derived endotoxins, which are already elevated because of the increased intestinal permeability in patients with cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…Previous studies reported that progression of liver cirrhosis was associated with intestinal barrier dysfunction leading to several defense mechanism abnormalities and increase in gut-derived endogenous Et [1,2]. Et was found to be associated with functional liver capacity and to increase with the progression of liver disease [10]. In this study, the risk of ACLF development was increased in patients with Child-Pugh class B disease compared with class A disease, and Et was associated with functional liver capacity.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Previous studies reported that progression of liver cirrhosis was associated with intestinal barrier dysfunction leading to several defense mechanism abnormalities and increase in gut-derived endogenous Et [1,2]. Et was found to be associated with functional liver capacity and to increase with the progression of liver disease [10]. In this study, the risk of ACLF development was increased in patients with Child-Pugh class B disease compared with class A disease, and Et was associated with functional liver capacity.…”
Section: Discussionsupporting
confidence: 53%
“…Previous studies have reported that EA was increased in patients with bacterial sepsis and related to the mortality risk, and that anti-Et treatment decreased EA [9]. Previous studies have also reported that increased EA in cirrhotic patients was associated with progression of liver cirrhosis [10] and EA was increased in patients with ALF [11]. EA associated with bacterial infection and inflammation may be involved in the pathophysiology of ACLF in liver cirrhosis patients.…”
Section: Introductionmentioning
confidence: 96%
“…Among the 12 patients in the PH group, 11 were taking proton pump inhibitors (PPIs), so the relationship between the ongoing use of PPIs for the treatment of varices was also taken into consideration (12)(13)(14)(15). It has been reported that the partial changes in the gut microbiota caused by PPI usage are similar to the changes caused by the progression of liver cirrhosis, and increased inflow of oral flora to the intestines might create an intestinal environment that is a risk factor for the progression of liver cirrhosis, spontaneous bacterial peritonitis, and hepatic encephalopathy (9,(16)(17)(18)(19). The levels of genera (Lactobacillales, Streptococcus, Selenomonas, Veillonella, Campylobacter, and Haemophilus) have been reported to be high in PPI users (20).…”
Section: Discussionmentioning
confidence: 99%
“…Since endotoxemia was first associated with human liver diseases in the 1970s, much attention has been paid to the importance of intestinal Et as a critical cofactor in severe liver diseases [ 2 , 3 ]. Et are frequently detected in patients with liver cirrhosis (LC) who present with no other evidence of Gram-negative infection, indicating that their condition is due to the impaired hepatic clearance of gut-derived Et that are normally absorbed from the gastrointestinal tract [ 4 , 5 ]. Increased Et levels due to increased intestinal permeability and insufficient Et clearance by the hepatic reticuloendothelial system, including macrophages (e.g., Kupffer cells), may lead to a marked increase in liver sensitivity to Et, resulting in spillover of the Et into the systemic circulation, which leads to extrahepatic manifestations consistent with liver injury [ 1 , 2 , 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Et are frequently detected in patients with liver cirrhosis (LC) who present with no other evidence of Gram-negative infection, indicating that their condition is due to the impaired hepatic clearance of gut-derived Et that are normally absorbed from the gastrointestinal tract [ 4 , 5 ]. Increased Et levels due to increased intestinal permeability and insufficient Et clearance by the hepatic reticuloendothelial system, including macrophages (e.g., Kupffer cells), may lead to a marked increase in liver sensitivity to Et, resulting in spillover of the Et into the systemic circulation, which leads to extrahepatic manifestations consistent with liver injury [ 1 , 2 , 3 , 4 , 5 , 6 ]. Increasing levels of Et in patients with LC are associated with hepatic failure, hepatic encephalopathy, and increased mortality [ 5 , 6 , 7 ]; they also trigger the hypercoagulability and cytokine cascade that precede multiple organ failure (MOF) (e.g., acute-on-chronic liver failure (ACLF)) [ 2 , 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%